(untitled) (American Journal of Pedagogical and Educational Research, 2023)
Teaching a second language involves the elicitation and acquisition of the general expressions that may be useful for students in everyday situations in which the target language is spoken. However, in the present context of strong scientific development, many learners are also faced with the need to become acquainted with terminology.